Plants Collection Enrichment of Purwodadi Botanic Garden Through Exploration in Alas Purwo National Park - Deden Mudiana; Elga Renjana; Elok Rifqi Firdiana; Linda Wige Ningrum; Melisnawati H Angio; Rony Irawanto (Jurnal Penelitian Kehutanan Wallacea, 2020)
Purwodadi Botanic Garden (KR Purwodadi) is an exsitu conservation institution for dry climate lowland plants aiming at saving and protecting biodiversity from extinction. In supporting exsitu conservation efforts, plant exploration activities in their natural habitat need to be carried out. Alas Purwo National Park has a lowland forest area with abundant plant diversity. In addition to functioning as a conservation forest, this area is also a natural and religious tourist attraction, so it is likely to undergo ecosystem damage. Therefore, this plant diversity study with theactivity of plants exploration and collection was carried out for the purpose of ex situ conservation in KR Purwodadi.This study was conducted in August to September 2019 using an explorative method. A total of 24 species were obtained, of which 8 species were not yet cultivated by KR Purwodadi. Besides, there were 5 species included in the IUCN red list, namely Aglaonema simplex, Brucea javanica, Cycas rumphii, Melanolepis multiglandulosa, and Musa acuminata. This study has increased the number of plant collections in KR Purwodadi and contribute positively to the comprehensiveness of plant species data in Alas Purwo National Park.